An LMI-based approach for the control of semi-active magnetorheological suspensions. Issue 2 (2020) - Begnis, Ruben; Panzani, Giulio; Brentari, Mirko; Zaccarian, Luca
Abstract: We address modelling and control of semi-active suspensions based on magnetorhe-ological (MR) fluids. We first introduce a saturation-based model of the underlying nonlinear phenomena, and combine the MR suspension with a quarter car model whose parameters resemble an SUV-like vehicle. Then we present simulation results to test the passenger comfort arising from the passive configuration (namely holding the input constant over the whole simulation) and the use of the Skyhook controller (which is adapted from its typical use in electrohydraulic suspensions). Finally, we propose LMI-based control designs exploiting an approximated model and typical generalized sector conditions for saturation nonlinearities. The simulation results show the advantages of the proposed design.